Economic Empowerment of Women through Resilient Agriculture Supply Chains : A Geospatial and Temporal Analysis in Southwestern Bangladesh - Makino, Yuka; Brahmam, Maya; Vargas, Juan Carlos; Yoon, Sulhee (World Bank, Washington, DC, 2019)
The purpose of this report is to present the findings from a study on the Economic Empowerment of Women through Resilient Agriculture Supply Chains: A Geospatial and temporal Analysis in Southwestern Bangladesh. Recognizing that a common weakness in transport corridors has been the lack of participation and limited benefits accruing to the communities through which a corridor passes, World Bank investments in transport infrastructure are increasingly complemented by activities that facilitate the competitiveness of micro and small enterprises and economic opportunities for women and other disadvantaged people and integrate gender-responsiveness into trade facilitation and logistics initiatives. This geospatial and temporal value chain analysis in southwestern Bangladesh adopts a five-step methodology which overlays economic and initial enterprise analysis along this transport corridor, analyzes human capital (with particular focus on women) and the labor force along transport corridors, considers risk management in the value chain analysis, evaluates the economic structure of a value chain, and restructures the opportunities and gaps in areas where agglomerated economic activities were identified. The report includes a total of four components: chapter one, Identification and characterization of agricultural products that are representative of women driven, small-to-medium enterprises (SMEs). Chapter two, a geographical diagnosis of the population’s sociodemographic and infrastructure conditions, and identification of constraints and opportunities regarding women-driven SMEs. Chapter three, value chain analysis for three agriculture products (fisheries, floriculture, and dairy) selected from chapter one. Analyses are represented in two formats: a) diagrams, and b) visualizations of spatial distribution. Chapter four, economic agglomeration and barriers for women-driven SME participation.